ANALISIS PERPUTARAN PERSEDIAAN DAMPAKNYA TERHADAP LABA BERSIH PADA APOTEK K24 BANDUNG - Windi Novianti; Koesheryatin Koesheryatin (JURISMA : Jurnal Riset Bisnis & Manajemen, 2014)
Inventory management is a technique for material related to inventory turns. Role in materials management inventory conducted with several inputs used are: the demand that occurred (demand) and costs associated with storage, Setra costs in case of lack of resources (short-age). The purpose of this study is to determine the velocity of inventory and net income in the state of Pharmacy K24period 2004-2009, and to know the inventory turnover has an impact on net income from 2004 to 2009 period. The method used in this study passing descriptive method with quantitative approach. Sample withdrawal techniques in this pnelitian nonprobability sampling using purposive sampling approach. Thus obtained samples of financial reports from 2004 until 2009. Technique data collecting taken is documentation, interviews and observation. While the data analysis using simple linear regression analysis, correlation, determination. Hypothesis test "t test" with the help of SPSS 17 for windows. The results show that the writer: (1) Development of inventory turns have increased, (2) Earnings Growth is always increasing and decreasing where the greatest decline occurred from 2008 to the year 2009 that is equal to -40.60% (3) does not affect Inventory Turnover significantly to the net profit attributable to other factors, as evidenced by the acquisition tcount -0567 <ttabrl 2.5706.Â